The Potential of Building High School Students' Vocabulary Using an iPod Touch and Gaming App - Jennifer Redd; Denise Schmidt-Crawford (Flexible Learning Association of New Zealand, 2011)
This study focused on the potential for building 25 high-school students' word knowledge by using a mobile learning device and gaming app. Using a game as an instructional tool is a portable way for students to engage with content. The amount of vocabulary mastered after using the app on the mobile device was examined in relation to a pre-test and a post-test, completed 3 weeks apart. The aspects investigated were the transfer potential of learning on a mobile device, and the variation in performance levels. The results indicated a direct correlation between the pre-test score as a predictor for the post-test score. Also, the choice of techniques used to play the app indicated that participants called upon the 'process of elimination' and 'roots/word parts' as tools to help them master the vocabulary. These findings point to the potential for incorporating a game as an instructional tool for vocabulary development.